2003
DOI: 10.3402/fnr.v47i4.1492
|View full text |Cite
|
Sign up to set email alerts
|

Calculations on the energy and nutrient content of kindergarten menus in Estonia

Abstract: Objective: To evaluate kindergarten menus in the frame of the National Health Programme for Children in Estonia in order to guarantee optimal food intake for children. Design: Five kindergarten menus were calculated in Tallinn and in a rural area in Estonia from February 1999 to December 2001, including both Russian and Estonian kindergartens with more than 700 children. The study was conducted using a Micro-Nutrica programme, the database with 700 foodstuffs and 900 readyto-eat meals, with 56 characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…About 75% of 3Á/6-year-old children in Estonia attend kindergarten. Analysis of kindergarten menus showed that calcium levels are 120Á/160% of the Estonian recommendations, provided mainly by dairy products, but that vitamin D content is very low, at 20Á/40% of recommended daily intake (RDI) (8).…”
Section: Introductionmentioning
confidence: 99%
“…About 75% of 3Á/6-year-old children in Estonia attend kindergarten. Analysis of kindergarten menus showed that calcium levels are 120Á/160% of the Estonian recommendations, provided mainly by dairy products, but that vitamin D content is very low, at 20Á/40% of recommended daily intake (RDI) (8).…”
Section: Introductionmentioning
confidence: 99%